An epidemiological outline of acne vulgaris in non-obese patients at a tertiary care center in south India - Mathai, Vinay Varghese; Gangaiah, Narendra; Thimmappa, Veena; Gundappa, Pavithra (International Journal of Research in Dermatology, 2022)
Background: A brief clinical vignette of the clinico-epidemiological data of acne vulgaris patients at a tertiary care center as the data seems particularly lacking in this field with respect to non-obese patients. Methods: A total of 80 patients who were not obese and had no features of virilization attending the dermatology outpatient department at Sri Siddhartha medical college, Tumkur were enrolled in this descriptional study. A detailed questionnaire and proforma was utilized to record data pertaining to history and physical examination. Results: A total of 55% (n=44) were males and 45% (n=36) were females and acne vulgaris was maximally seen in the 20-29 years age group, 60% (n=48). In this study 50% (n=40) of the study subjects were students, 22.5% (n=18) housewives.76.5% (n=61) subjects had presented with complaints of acne over the face. The 37% (n=30) subjects who presented had a duration of onset less than 6 months. All subjects had involvement of the cheek and 27.5% (n=22) had involvement of chest and back. Mild grade of acne vulgaris was observed in 72% (n=58), moderate grade in 23% (n=18), severe and very severe grade in 5% (n=4). Conclusions: Acne vulgaris is one the most common dermatoses encountered by dermatologists. Any new information in the clinico-epidemiological aspects of this frequently met condition will help in preventive and management of acne vulgaris especially catering to the patient needs.